Survival of purebred and hybrid Serrasalmidae under low water temperature conditions - Fernandes, Erica Machado [UNESP]; de Almeida, Luis Carlos Ferreira [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Lattanzi, Gabriel Rinaldi [UNESP]; Gervaz, Washington Rocha [UNESP]; Leonardo, Antônio Fernando; Neto, Rafael Vilhena Reis [UNESP] (Elsevier, 2018)
The aim of the study was to evaluate the survival of Serrasalmidaes fish, pure and hybrid, during periods of low temperature. The experiment was carried out from June to August 2016 (51 days) in an aquaculture station of São Paulo Agribusiness Technology Agency, Brazil. A diallel crossbreeding between pacu and tambaqui was performed by artificial reproduction, generating four genetic groups: pacu (♂ pacu × ♀ pacu), tambaqui (♂ tambaqui × ♀ tambaqui), paqui (♂ tambaqui × ♀ pacu), and tambacu (♂ pacu × ♀ tambaqui). Fish were distributed in 24 experimental plots (110 fingerlings of each groups per plot) and were fed twice daily with commercial diets containing three different levels of crude protein (CP): 24%, 28% and 32%. When the water temperature showed successive decreases due to the environmental climatic conditions, the ponds were monitored daily to record the mortality. The data on number of days of life of animals were submitted to Cox multivariate regression analysis to test the effects of the genetic group, CP levels and the interaction between the two factors. Kaplan-Meier survival curves were adjusted for factors that had a significant effect on the Cox regression analysis. The pacu group presented higher survival than other groups, regardless of the CP level in the diet. The tambaqui and paqui groups were more susceptible to environmental conditions, especially when fed a diet containing a higher level of CP. Overall, purebred pacu presented greater adaptation to the production conditions in the region where the experiment was carried out. However, if the aim is the production of hybrid fish, crosses between pacu males and tambaqui females (Tambacu) generate fish that are resistant to low temperatures.
Keywords: Cold tolerance; Colossoma macropomum; Piaractus mesopotamicus; Survival curves